2014
DOI: 10.1080/13811118.2013.826154
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Child Psychopathology and Suicide Attempts among Children of Parents with Alcohol Use Disorder

Abstract: Parents with psychopathology such as alcohol use disorder (AUD) that confers risk for suicide attempt (SA) may have children who are more likely to develop such psychopathology and to attempt suicide, suggesting that risk may be “transmitted” from parents to children. We examined this phenomenon during the transition from childhood to adolescence, when risk for SA increases dramatically. A cohort of 418 children were examined at average age 9.4 (range 7–14) years at enrollment (Time 1, childhood) and approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…Sensitivity analyses showed that heterogeneity could only be slightly reduced by excluding those studies with a followup <3 years (OR = 6.67; I 2 = 58%) resulting in a slightly higher estimate. Based on the Galbraith Plot, three studies were excluded (Conner et al, 2014;Fergusson et al, 2005;Miranda et al, 2014) and the analysis yielded a lower but similar estimate (OR = 4.93) with no heterogeneity (Figure 3).…”
Section: Previous Suicidal Thoughts and Behaviorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sensitivity analyses showed that heterogeneity could only be slightly reduced by excluding those studies with a followup <3 years (OR = 6.67; I 2 = 58%) resulting in a slightly higher estimate. Based on the Galbraith Plot, three studies were excluded (Conner et al, 2014;Fergusson et al, 2005;Miranda et al, 2014) and the analysis yielded a lower but similar estimate (OR = 4.93) with no heterogeneity (Figure 3).…”
Section: Previous Suicidal Thoughts and Behaviorsmentioning
confidence: 97%
“…Over half (61%) of the studies achieved ≥ 6 stars. Most of the studies (69%) recruited the sample from general or student population, but other studies recruited specific high-risk groups (e.g., lesbian, gay, and bisexuals; with depressive symptoms or disruptive behaviors; or offspring of alcoholic parents) (Brezo et al, 2007;Conner et al, 2014;Lambert et al, 2008;Lewinsohn et al, 2001;McKeown et al, 1998;Miranda et al, 2014;Mustanski and Liu, 2013;Nrugham et al, 2008;Scott et al, 2015). In two studies (8%), previous SITB had been clinically validated (Brezo et al, 2007;Finkelstein et al, 2015).…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the literature, involvement in bullying and being a victim of aggression are associated with an increased risk of suicide. 26,27 Family and school are the most In this study, it was observed that suicidal ideation was described in 14 of the cases studied. A suicide attempt, which is one of the criteria for inclusion of cases in this study, was present in all medical records analyzed.…”
Section: Discussionmentioning
confidence: 69%
“…[24][25][26] Along the same lines, it also appears that paternal psychopathology is an important risk factor for attempted suicide in the offspring. 27 Psychopathologies in the family, such as parental mood and personality disorders and substance abuse, have been demonstrated to increase child risk of non-fatal suicidal behavior. 2 Out of 54 studies identified for a review, nine studies indicated a significantly increased risk of offspring suicide-related thoughts suicide attempts and suicide among those exposed to maternal suicide attempts and suicide in childhood or adolescence.…”
Section: Discussionmentioning
confidence: 99%